on some normal hematological values in foals and arabian horses at different ages - Sultan, A. Sh. (The Iraqi Journal of Veterinary Medicine, 2001)
Hematological values of twenty normal male foals at 1-6 months , 7-12 months and sixty Arabian horses at 1-5 years old were estimated respectively. Red blood cell count ( RBCS), hemoglobin concentration (Hb), packed cell volume (PCV% ), mean corpuscular volume (MCV) ; mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), differential leukocyte count, total serum protein were determined using several laboratory techniques. These changes of these parameters were presented in tables in relation to the ages of these animals.